Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Unveiling mechanistic insights of inactivated Aspergillus niger spore by fishery-waste-derived chitosan via synchrotron radiation tomography - Ying-Chen Chen; Chih-Huang Weng; Chun-Chieh Wang; Zi-Jing Lin; Shang-Ming Huang; Girma Sisay Wolde; Jenn-Wen Huang; Mo Da-Sang Hua; Yao-Tung Lin (Carbohydrate Polymers, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Metallothioneins protect against isoconazole nitrate-induced antitumor activity through the maintenance of cellular redox homeostasis in hepatocellular carcinoma - Chun-fen Mo; Ya-ruo Lei; Jun Lin; Yi Liu; Zhi-wei Zhao; Wen-jing Xiao; Wen-bai Yan; Wei-wei Zhang (Chemico-Biological Interactions, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

Solid-state fermentation of Limosilactobacillus fermentum and lysine addition to improve the cooking and eating quality of high-fiber rice noodles - Yakun Song; Jing Lin; Lijuan Luo; Zihan Chen; Weiling Mo; Xiangjin Fu; Chun Liu (Journal of Cereal Science, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Identification and characterisation of microplastics released from plastic-coated paper cups using micro-Raman spectroscopy - Tianlong Zhang; Jia-Ling Hu; Yipin Duan; Sheng Chen; Dan Li; Ben Dong; Ming-Zhen Mo; Jing Wang; Jian-Guo Zheng; Huai-Ning Zhong; Qin-Bao Lin (Food Control, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Evaluation of in vitro toxicity information for zebrafish as a promising alternative for chemical hazard and risk assessment - Jing Yang; Yolina Yu Lin Wang; Syed Shabi Ul Hassan Kazmi; Jiezhang Mo; Hailin Fan; Yuwen Wang; Wenhua Liu; Zhen Wang (Science of The Total Environment, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

Two new phthalide derivatives from the endophytic fungus Penicillium vulpinum isolated from Sophora tonkinensis - Yuyue Qin; Xiaobo Liu; Jing Lin; Jingying Huang; Xiaofei Jiang; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Deuterium excess record in a southern Tibetan ice core and its potential climatic implications - Huabiao Zhao; Baiqing Xu; Tandong Yao; Guangjian Wu; Shubiao Lin; Jing Gao; Mo Wang (Climate Dynamics, 2012)

Matrix metalloproteinase-9 as new biomarkers of severity in multiple organ dysfunction syndrome caused by trauma and infection - Lin Teng; Min Yu; Jun-ming Li; Hua Tang; Jing Yu; Li-hua Mo; Jing Jin; Xian-zhe Liu (Molecular and Cellular Biochemistry, 2012)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)